THE COMPLEMENTARY RELATIONSHIP BETWEEN ORGANIZATIONAL DNA AND AUTHENTIZOTIC ORGANIZATIONS AND IMPACTS IN ORGANIZATIONAL EMBEDDEDNESS: AN ANALYTICAL STUDY OF THE OPINIONS OF AS SAMPLE OF LECTURERS AT THE UNIVERSITY OF DIYALA - Lecture: Mohammed Mahmood Thamer; Professor: Ahmed Ali Hussain (Scholars Digest Publishing, 2025)
This study aims to identify the role played by the complementary relationship between regulatory genes and affinity organizations and their impact on organizational stability. An Iraqi university, the University of Diyala, was chosen as a field of study through a sample of (304) lecturers from the total study population of (1459). A questionnaire valid for statistical analysis was distributed. Conducting personal interviews with leaders in the field of work. To achieve the study objectives and hypotheses, a hypothetical scheme was developed through which the nature of the logical relationships between the study variables and their dimensions was determined. Descriptive statistics, inferential statistics and tests were also used. The statistical analysis program (AmosV.26) (SPSSV.29) was used to test the study objectives and hypotheses. The study came out with a set of conclusions that matched its hypotheses, the most important of which were: 1-Achieving organizational Embeddedness at the University of Diyala from the study sample is linked to strengthening and reinforcing the relationship between organizational dna and the Authentizotic organizations, as the impact increases through them in achieving stability first, and then focusing on providing all elements of academic work that enhance the level of competitive strategic performance second. 2-At the university level, where the relationship and influence between the variables are strong, this result confirms the importance of the variables in the universities of the study sample. The study concluded with a set of recommendations and proposals that educational institutions see as necessary to adopt.
Keywords: Organizational DNA, Authentizotic organizations, Organizational Embeddedness